An electrocardiographic, molecular and biochemical approach to explore the cardioprotective effect of vasopressin and milrinone against phosphide toxicity in rats. (June 2015) - Jafari, Abbas; Baghaei, Amir; Solgi, Reza; Baeeri, Maryam; Chamanara, Mohsen; Hassani, Shokoufeh; Gholami, Mahdi; Ostad, Seyed Nasser; Sharifzadeh, Moahmmad; Abdollahi, Mohammad
Highlights: AlP exposure led to severe cardiovascular toxicity. AlP caused mitochondrial dysfunction and apoptosis in cardiomyocytes. Vasopressin restored hypotension and ECG abnormalities after AlP exposure. Milrinone improved cardiac function and potentiated the protective effect of AVP. AlP-induced oxidative stress and apoptosis were mitigated by AVP and milrinone. Graphical Abstract: Abstract: The present study was conducted to identify the protective effect of vasopressin (AVP) and milrinone on cardiovascular function, mitochondrial complex activities, cellular ATP reserve, oxidative stress, and apoptosis in rats poisoned by aluminum phosphide (AlP). Rats were divided into five groups (n = 12) including control, AlP (12.5 mg/kg), AlP + AVP (2.0 Units/kg), AlP + milrinone (0.25 mg/kg) and AlP + AVP + milrinone. After treatment, the animals were connected to an electronic cardiovascular monitoring device to monitor electrocardiographic (ECG) parameter. Finally, oxidative stress biomarkers, mitochondrial complex activities, ADP/ATP ratio and apoptosis were evaluated on the heart tissues. Results indicated that AlP administration induced ECG abnormalities along with a decline in blood pressure and heart rate. AVP and milrinone significantly ameliorated these changes in all treated groups. Considerable protective effects on oxidative stress biomarkers, complex IV activity, ADP/ATP ratio and caspase-3 and -9 activities in treated groups were also found. These findings were supported by flow cytometry assay of cardiomyocytes. In conclusion, administration of AVP and milrinone, not only improve cardiovascular functions in AlP poisoned rats in the short time, but after a long time can also restore mitochondrial function and ATP level and reduce the oxidative damage, which prevent cardiomyocytes from entering the apoptotic phase.